2012
DOI: 10.1542/peds.2011-2173
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic Effect of Breast Milk Versus Sucrose for Analgesia During Heel Lance in Late Preterm Infants

Abstract: From this study, it cannot be concluded that breast milk has a better analgesic effect than sucrose in late preterm infants. From the results, it follows with 95% confidence that the analgesic effect of breast milk is not >1.6 points better and not > 2.8 points worse on the PIPP scale (SD 3.7) than the analgesic effect of sucrose in late preterm infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 19 publications
2
28
0
8
Order By: Relevance
“…Codipietro et al (2008) however found breast feeding to be the most effective strategy for procedural pain comfort. Simonse et al (2010) found sucrose and breast milk to be equally effective in reducing pain responses during procedures. A systematic review by Shah et al (2007) analysed 11 eligible studies comparing breast feeding or the use of expressed breast milk (EBM) verses no treatment and other measures who then report on physiological/validated pain scores.…”
Section: The Combined Use Of Sucrose With Other Strategiesmentioning
confidence: 99%
“…Codipietro et al (2008) however found breast feeding to be the most effective strategy for procedural pain comfort. Simonse et al (2010) found sucrose and breast milk to be equally effective in reducing pain responses during procedures. A systematic review by Shah et al (2007) analysed 11 eligible studies comparing breast feeding or the use of expressed breast milk (EBM) verses no treatment and other measures who then report on physiological/validated pain scores.…”
Section: The Combined Use Of Sucrose With Other Strategiesmentioning
confidence: 99%
“…Hasil penelitian menunjukkan bahwa tidak ada perbedaan yang signifikan, dengan nilai p=0,076. Hal ini sesuai dengan penelitian yang dilakukan Simonse, et al (2012) yang juga membandingkan ASI dengan sukrosa pada prosedur heel lance bayi prematur, Simonse menjelaskan bahwa tidak ada perbedaan yang signifikan, nilai rata-rata menunjukkan perbedaan, pada kelompok ASI 6,1 dan kelompok sukrosa nilai rata-rata adalah 5,5 dengan perbedaan rata-rata 0,6 pada kepercayaan 95%, p=0,58. Sehingga dapat disimpulkan bahwa ASI tidak memiliki efek analgetik lebih baik daripada sukrosa, begitu juga dengan sukrosa juga tidak memiliki efek analgetik lebih baik dari pada ASI.…”
Section: Perbedaan Respon Nyeri Kelompokunclassified
“…The involvement of the mother is recommended through skin-to-skin or breast-feeding during a single sampling. Several studies have shown how breastfeeding during a painful procedure reduces the stress in newborn [3]. …”
mentioning
confidence: 99%